Food texture design by 3D printing: a review - Pereira, Tatiana (2021)
An important factor in consumers’ acceptability, beyond visual appearance and taste, is food texture. The elderly and people with dysphagia are more likely to present malnourishment due to visually and texturally unappealing food. Three-dimensional Printing is an additive manufacturing technology that can aid the food industry in developing novel and more complex food products and has the potential to produce tailored foods for specific needs. As a technology that builds food products layer by layer, 3D Printing can present a new methodology to design realistic food textures by the precise placement of texturing elements in the food, printing of multi-material products, and design of complex internal structures. This paper intends to review the existing work on 3D food printing and discuss the recent developments concerning food texture design. Advantages and limitations of 3D Printing in the food industry, the material-based printability and model-based texture, and the future trends in 3D Printing, including numerical simulations, incorporation of cooking technology to the printing, and 4D modifications are discussed. Key challenges for the mainstream adoption of 3D Printing are also elaborated on.